Secretory Phospholipases A2 in Plants - Mariani, María Elisa; Fidelio, Gerardo Daniel (Frontiers in Plant Science, 2019)
Secreted phospholipases in plants (sPLA2) are a growing group of enzymes that catalyze the hydrolysis of sn-2 glycerophospholipids to lysophospholipids and free fatty acids. Until today, around only twenty sPLA2s were reported from plants. This review discusses the newly acquired information on plant sPLA2s including molecular, biochemical, catalytic and functional aspects. The comparative analysis also includes phylogenetic, evolutionary and tridimensional structure. The observations with emphasis in Glycine max sPLA2 are compared with the available data reported for all plants sPLA2s and with those described for animals (mainly from pancreatic juice and venoms sources).